When All Hands Are Not on Deck: Intergovernmental Relations and the Fight against COVID-19 Pandemic in the Nigerian Federation. (2nd January 2022) - Aniche, Ernest Toochi; Iwuoha, Victor Chidubem; Alumona, Ikenna Mike; Okwueze, Felicia Osondu
ABSTRACT: The defects and susceptibility of the Nigerian federalism are more pronounced at this period of the Covid-19 pandemic. Existing studies are yet to articulate how the states, in the formulation and enforcement of the lockdown and physical distancing policies, infringed on the federal exclusive matters by closing land borders, airports and imposing partial banking services. There is selective provision/distribution of healthcare facilities and stimulus packages and palliatives across the states by the federal government. The objective of this study is to examine how the conflicting nature of intergovernmental relations is implicated in the level of implementation of containment policies/strategies towards the fight against the Covid-19 pandemic in Nigeria. Based on content analysis and the functional-process theory, the article argued that the cantankerous/imploding disconnects between the federal and state governments–obscuring the making and implementation of harmonised and coordinated pandemic containment policies–constitute key impediment to the fight against Covid-19 in Nigeria.